Language curriculum design - Nation, I. S. P. (ESL & applied linguistics professional series, 2010)
"Case studies are a powerful pedagogical tool for illuminating constructs and models in real-life contexts. Covering a wide range of teachingùlearning contexts and offering in-depth analyses of ESL/EFL language curriculum design issues, this casebook is distinctive and unique in that each case draws on and is clearly linked to a single model presented in Nation and Macalister's Language Curriculum Design (www.routledge. com/9780415806060), giving the book a high degree of coherence. A short commentary by the editors after each case highlights features of note and/or issues arising from it. This is a versatile text, designed to work as a companion to Language Curriculum Design (adding meaning and depth to the model presented there by relating it to a range of applications), as a stand-alone text, or as a resource for language teacher trainees, teacher educators, practicing teachers, program administrators, and materials writers in the field."--Jacket.